The Arabidopsis Chromatin-Modifying Nuclear siRNA Pathway Involves a Nucleolar RNA Processing Center - Pontes, O.; Li, C.F.; Costa Nunes, P.; Haag, J.; Ream, T.; Vitins, A.; Jacobsen, S.E.; Jacobsen, S.E.
In Arabidopsis thaliana, small interfering RNAs (siRNAs)direct cytosine methylation at endogenous DNA repeats in a pathway involving two forms of nuclear RNA polymerase IV (Pol IVa and Pol IVb), RNA-DEPENDENT RNA POLYMERASE 2 (RDR2), DICER-LIKE 3 (DCL3), ARGONAUTE4 (AGO4), the chromatin remodeler DRD1, and the de novo cytosinemethyltransferase DRM2. We show that RDR2, DCL3, AGO4, and NRPD1b (the largest subunit of Pol IVb)colocalize with siRNAs within the nucleolus. By contrast, Pol IVa and DRD1 are external to the nucleolus and colocalize with endogenous repeat loci. Mutation-induced loss of pathway proteins causes downstream proteins to mislocalize, revealing their order of action. Pol IVa acts first, and its localization is RNA dependent, suggesting an RNA template. We hypothesize that maintenance of the heterochromatic state involves locus-specific Pol IVa transcription followed by siRNA production and assembly of AGO4- and RPD1b-containing silencing complexes within nucleolar processing centers.